Quality of life in road traffic accident survivors - Kovačević Jelena; Miškulin Maja; Ličanin Matea Matić; Barać Josip; Biuk Dubravka; Palenkić Hrvoje; Matić Suzana; Kristić Marinela; Biuk Egon; Miškulin Ivan (Sciendo, 2020)
The loss of quality of life is the major consequence following a non-fatal road traffic accident (RTA). Previous research regarding quality of life did not include uninjured RTA survivors. The research aim was thus to evaluate the quality of life of the RTA survivors regardless of whether or not they sustained injures, and to identify factors associated with decreased quality of life after the RTA.